INTERACTIVE NETWORK RESOURCES FOR NATURAL SCIENCE EDUCATION AND RESEARCH - Michail I. Mazuritsky; Alexandr V. Soldatov (Высшее образование в России)
The paper discusses the design of the e-learning system used in the Southern Federal University andrelated features in the context of the education for skilled workers. This approach uses access to the scientific and technology laboratory equipment either for provisioning the individualized educational programs or to enable the students who are unable to attend a conventional laboratory for a variety of reasons (disability, part-time study, etc.) to conduct the experimental work. Our learning strategy is the reverse of that is used traditionally. We suggest to start with the introduction to the practical applications of science and technology relevant to the current job market, and study the general laws and theoretical principles afterwards, to deepen understanding and achieve the educational goals.